A Balāghah Analysis of Majāz Mursal Usage in the Verses of the Qur’an, Juz 14 - Hilda Khaerunnisa; Farhan Firdaus (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
The language used in the Qur’an represents the most beautiful form of the Arabic language, and no written work is able to equal its eloquence. Among the aspects of this linguistic beauty is the extensive use of rhetorical devices, one of which is majaz mursal, found in the verses of the Qur’an, particularly in the fourteenth juz. The purpose of this study is to identify the verses in the fourteenth juz that contain majaz mursal and to analyze them based on the various types of ‘alaqah. The research employs a qualitative approach using a descriptive-analytical method. The findings indicate that there are twenty-six verses in the fourteenth juz that contain majaz mursal, distributed across Surah Al-Ḥijr and An-Naḥl. The types of ‘alaqah identified include juz’iyyah, kulliyyah, mahaliyyah, ḥāliyyah, musabbabiyyah, and al-umūm. These findings demonstrate that majaz mursal enriches the meaning of the Qur’an and deepens the understanding of divine messages, serving as a bridge between linguistic beauty and the depth of meaning that characterizes the Qur’anic style.